Genetic and facial structure of quaternary deposits on the territory of the Gomel chemical plant - Shershnyov, Oleg V.; Pavlovskii, Aleksandr I. (Journal of the Belarusian State University. Geography and Geology, 2019)
Analysis of lithological and genetic features quaternary deposits within the influence zone of industrial objects continues to be an urgent task of modern geology and geoecology. The article presents the results of studies of the lithologic features of quaternary deposits of the first from the surface of the low permeable layer underlying the ground aquifer within the sanitary protection zone of the Gomel chemical plant (GCP). In its structure, genetic types, groups of facies and facial varieties were identified. Large-scale (1 : 25 000) mapping of the established facies of quaternary deposits has been carried out. The present-day appearance of the formed natural and technogenic landscape has been studied. It has been established technolithomorphological changes of the geological and geomorphological basis of natural landscapes took place in the production zone of the plant. Facies of technogenic genesis has been identified.
Keywords: quaternary deposits; low permeable layers; genetic type; facies; technogenic deposits